Mapping HOTS in Textbook Assessment Items: Implications for Instructional and Learning Quality - Yeni Witdianti; Nursalim; Juwilsi Thianci Rawung; Martina L Suarlembit (Jurnal Pendidikan Indonesia, 2026)
The main problem in Indonesian language learning at the high school level is the low application of Higher Order Thinking Skills (HOTS) aspects in evaluation questions, which impacts the development of students' critical, analytical, and creative thinking abilities. This study is motivated by the need to improve the quality of learning thru assessments that demand higher-order thinking skills. This study aims to analyze and evaluate the representation of HOTS aspects in the evaluation questions within the Tiga Serangkai Indonesian Language textbook for SMA Class X, and to assess its implications for the quality of learning. The research subject is the evaluation questions in the Indonesian textbook "Tiga Serangkai" for high school students in Class X, with a total of 60 questions analyzed. Data collection was carried out using the content analysis method, with the instrument being a categorization sheet based on the revised Bloom's taxonomy (C4–C6). Data analysis techniques included identifying, classifying, and interpreting the cognitive levels of the evaluation questions. The research results indicate that the proportion of questions accommodating HOTS aspects is still very low, with the majority of questions falling into the low-level thinking category (C1 and C2). This finding indicates the need for developing HOTS-based evaluation questions so that Indonesian language learning can be more effective in fostering higher-order thinking skills. The implications of this research underscore the importance of involving textbook authors, teachers, and education policymakers in designing evaluation questions that emphasize HOTS aspects to prepare students for the challenges of the 21st century.